Analisis Kesulitan Keterampilan Menulis Karangan Deskripsi Peserta Didik Fase B di Sekolah Dasar - Hiskia Sitorus; Radni Defri Sagita; Rahmadarati Rahmadarati; Chandra Chandra; Ari Suriani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to identify the level of difficulty and ability to write descriptive essays for phase B students in class IV in elementary school. This research uses a descriptive qualitative method with a case method approach. Data was collected through observation, interviews with students, and document analysis of students' writing results. The results of the research show that phase B students in class IV in elementary schools experience difficulties in writing descriptive essays in several aspects, namely: It is difficult for students to find a title that suits the topic. Students can create text that matches the title, but the content of the idea is incomplete. Students have not used all their five senses to write descriptive text. Students have difficulty writing paragraphs that have cohesion and coherence. Students have difficulty using the correct choice of words (diction) according to the sentence. It is difficult for students to use the correct spelling according to the rules. Students have difficulty using punctuation marks.